Environmental Enrichment and Metformin Combination Improves Cognitive Function through BDNF and HPA Axis in Chronically Stressed Rats - Bhagya, Venkanna Rao; Tilak, Kariyanna; Kanimozhi, Loganathan; Sushma, Raju (Current Alzheimer Research, 2025)
IntroductionChronic stress is a major global health issue linked to conditions such as anxiety, depression, and cognitive decline. In rodent studies, chronic immobilization stress (CIS) is commonly used to investigate the neuropsychological effects of prolonged stress, leading to behaviours such as anhedonia, anxiety, and depressive-like symptoms. An enriched environment (EE) provides physical, cognitive, and sensory stimulation, which promotes social interaction, supports brain development, and can enhance the effectiveness of pharmacological treatments, improving overall therapeutic outcomes. Metformin, commonly prescribed for type 2 diabetes, has antidiabetic effects and helps reduce oxidative stress, inflammation, and cell death in the brain, which may contribute to its neuroprotective properties. This study aims to evaluate the effectiveness of metformin, an enriched environment (EE), and its combination in alleviating anxiety and depression-like behaviours, memory impairments, and metabolic changes.Materials and MethodsRats were exposed to chronic immobilization stress (CIS) for 2 hours per day over a period of 10 days, followed by 14 days of treatment with metformin (200 mg/kg) and 6 hours of daily exposure to an enriched environment (EE). Behavioural tests, including the open field test (OFT), elevated plus maze (EPM), sucrose preference test (SPT), and novel object recognition test (NORT), were conducted. After completing the behavioural assessments, the animals were euthanized, and their plasma levels of corticosterone (CORT), high-density lipoprotein (HDL), low-density lipoprotein (LDL), cholesterol, triglycerides, and glucose were measured. Additionally, the concentration of brain-derived neurotrophic factor (BDNF) in the hippocampus was analysed.ResultsRats exposed to chronic immobilization stress (CIS) exhibited increased anxiety and depressive-like behaviours, as well as poor performance in the novel object recognition test (NORT). These behavioural changes were linked to elevated levels of plasma corticosterone (CORT), LDL, cholesterol, triglycerides, and glucose, along with decreased HDL levels and lower hippocampal BDNF. Treatment with metformin, an enriched environment (EE), or their combination alleviated these effects, improving exploratory behaviour, sucrose preference, and recognition memory and reducing anxiety-like behaviours. These benefits were accompanied by increased hippocampal BDNF expression, elevated plasma HDL, and reduced levels of CORT, LDL, cholesterol, triglycerides, and glucose.DiscussionThe combination of metformin and an enriched environment completely restored cognitive impairment and metabolic alterations in chronic stress conditions. Metformin’s ability to improve energy metabolism and reduce oxidative stress could be further enhanced in an enriched environment, which promotes cognitive function and resilience to stress.ConclusionTherefore, evidence suggests that EE can positively influence the outcomes of the neuroprotective effects of metformin and present promising therapeutic approaches for mitigating stress-induced behavioural and biochemical alterations.
Keywords: enriched environment